2
$\begingroup$

I am trying to solve the underneath problem. I managed to get the initial proof but to generalize on $n+1$ I failed.

Show that for any natural $n\geq 2 $ and any real $a_i$ we have : $$(\sum_{i=1}^n a_i)^2 \leq 2^{n-1}\sum_{i=1}^n a_i^2.$$

Thanks

$\endgroup$
3
$\begingroup$

For the inductive step you may apply the $n$-case inequality to $$a_1,a_2,\dots, a_{n-1},(a_n+a_{n+1}).$$ Hence $$(\sum_{i=1}^{n+1} a_i)^2=(\sum_{i=1}^{n-1} a_i+(a_n+a_{n+1}))^2 \leq 2^{n-1}\left(\sum_{i=1}^{n-1} a_i^2+(a_n+a_{n+1})^2\right).$$ So it remains to show that $$2^{n-1}\left(\sum_{i=1}^{n-1} a_i^2+(a_n+a_{n+1})^2\right)\leq 2^{n}\sum_{i=1}^{n+1} a_i^2$$ that is $$\sum_{i=1}^{n-1} a_i^2+(a_n+a_{n+1})^2\leq 2\sum_{i=1}^{n-1} a_i^2+2a_n^2+2a_{n+1}^2.$$ Can you take it from here?

$\endgroup$
  • $\begingroup$ Enough clear, I guess I have to work more on the abstraction model to get full scope of the problem. Thanks a lot for your precious Help. ( Sorry for the Vote, I need 15 reputations to vote, and I just posted my first question here ) $\endgroup$ – SAM.Am Sep 4 '19 at 10:10
3
$\begingroup$

I see 3 solutions of the above inequality:

$$(\sum_{i=1}^n a_i)^2 \leq 2^{n-1}\sum_{i=1}^n a_i^2.$$ Let me join the fun:

$$(\sum_{i=1}^n a_i)^2\ = \ \sum_{i=1}^n\,(a_i\cdot\sum_{j=1}^n a_j)\ \le \ \frac 12\cdot \sum_{i=1}^n\,(n\!\cdot\! a_i^2+\sum_{j=1}^n a_j^2) \ =\ n\cdot\sum_{k=1}^n a_k^2 $$ i.e. $$(\sum_{i=1}^n a_i)^2\ \le\ n\cdot\sum_{i=1}^n a_i^2 $$

which is clearly much better than our original OP's goal -- indeed, $\ \forall_{n=1}^\infty\, n\le 2^{n-1}.$

$\endgroup$
2
$\begingroup$

Use the inequality $(a+b)^{2} \leq 2(a^{2}+b^{2})$. If $s_n= \sum\limits_{k=1}^{n} a_i$ then $(s_n+a_{n+1})^{2} \leq 2(s_n^{2}+a_{n+1}^{2}) \leq 2(2^{n}\sum\limits_{k=1}^{n} a_i^{2}+a_{n+1})^{2}$. Can you take over from here?

$\endgroup$
  • $\begingroup$ yes, I got it. it's clear now. Thanks $\endgroup$ – SAM.Am Sep 4 '19 at 21:51
2
$\begingroup$

Without induction we have $$ 2^{n-1}\sum_{i=1}^na_i^2-(\sum_{i=1}^na_i)^2= $$ $$= 2^{n-1}\sum_{i=1}^na_i^2-\sum_{i=1}^na_i^2-\sum_{1\le i<j\le n}2a_ia_j=$$ $$= (2^{n-1}-n)\sum_{i=1}^na_i^2+(n-1)\sum_{i-1}^na_i^2-\sum_{1\le i<j\le n}2a_ia_j=$$ $$=(2^{n-1}-n)\sum_{i=1}^na_i^2\,+\sum_{1\le i<j\le n}(a_i-a_j)^2\ge 0$$ because $2^{n-1}- n\ge 0.$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.